Correction: 2D phosphorene as a water splitting photocatalyst: fundamentals to applications. Issue 4 (22nd March 2016) - Rahman, Mohammad Ziaur; Kwong, Chi Wai; Davey, Kenneth; Qiao, Shi Zhang
Abstract : Correction for '2D phosphorene as a water splitting photocatalyst: fundamentals to applications' by Mohammad Ziaur Rahman et al., Energy Environ. Sci., 2016, 9, 709–728.